A Romantic Life Dedicated to Science: André-Marie Ampère’s Autobiography - Moruno, Dolores Martín (Teorie vědy / Theory of Science, 2011)
This article explores André-Marie Ampère's autobiography in order to analyse the dynamics of science in early 19th century French institutions. According to recent works that have emphasised the value of biographies in the history of science, this study examines Ampère's public self-representation to show the cultural transformations of a life dedicated to science in post-revolutionary French society. With this aim, I have interpreted this manuscript as an outstanding example of the scientific rhetoric flourishing in early 19th century French Romanticism, which celebrated the life and works of men of science by means of biographies. Following this approach, Ampère's account has been analysed in relation to certain commonplaces shared with other autobiographies of that time, such as his traumatic experience linked to the French Revolution. Finally, this article discusses Ampère's autobiography as revealing an emerging model of scientific personae, i.e. a new collective way of thinking, feeling and perceiving, which announced the category of the modern scientist.